2016
DOI: 10.1002/osp4.78
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HbA1c and circulating and adipose tissue androgen levels in overweight‐obese women with polycystic ovary syndrome in response to electroacupuncture

Abstract: SummaryAimInsulin sensitivity is ~40% lower in women with polycystic ovary syndrome (PCOS) than in controls. We tested the hypothesis that 5 weeks of electroacupuncture treatment improves glucose regulation and androgen levels in overweight/obese women with PCOS.Material and MethodsSeventeen women with PCOS, aged 18 to 38 years, with a body mass index (BMI) ≥25 kg/m2 and diagnosed with PCOS were included in this experimental and feasibility study and subjected to five weeks of electroacupuncture treatments thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…It has been reported that proNGF acts as an inducer of sympathetic denervation in peripheral tissues (37,38). Our data are consistent with a possible increased conversion of proNGF into mNGF (39), which would support sympathetic activity far beyond the stimulation period with possible long-lasting beneficial effects on adipose tissue metabolism (36,40) and glucose uptake (26). Serotonin affects glucose homeostasis and insulin resistance via vagal afferent serotonergic neurons and receptors in peripheral tissue.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that proNGF acts as an inducer of sympathetic denervation in peripheral tissues (37,38). Our data are consistent with a possible increased conversion of proNGF into mNGF (39), which would support sympathetic activity far beyond the stimulation period with possible long-lasting beneficial effects on adipose tissue metabolism (36,40) and glucose uptake (26). Serotonin affects glucose homeostasis and insulin resistance via vagal afferent serotonergic neurons and receptors in peripheral tissue.…”
Section: Discussionsupporting
confidence: 87%
“…We used a Western style of acupuncture (26). In brief, acupuncture needles were placed bilaterally in the abdominal muscle, in the quadriceps muscles, and in the muscles below the medial side of the knee, all in somatic segments corresponding to the innervation of the ovaries and pancreas.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, hyperandrogenism is related to the high sympathetic nerve activity in women with the syndrome and the activity of these nerves increasing the response to hyperinsulinemia. 8 The reduction in fertility rates with an increase in free androgen content (ITA), obtained from total testosterone x 100/SHBG calculation in women who have insulin resistance adds to the evidence that insulin resistance increases hyperinsulinemia and vice versa. This may indicate that these factors negatively affect the ovaries and consequently diminish fertility.…”
Section: Polycystic Ovarian Syndrome (Pcos) X Hyperandrogenismmentioning
confidence: 99%
“…12,14 In polycystic ovary syndrome, acupuncture could affect glucose uptake in the skeletal tissue, 15,16 might decrease hyperinsulinemia, and might increase insulin clearance. 17 The aim of this article is to provide an overview of the current literature evaluating acupuncture's effects on IVF outcomes.…”
Section: Introductionmentioning
confidence: 99%